Structuring of solution processed and thermally evaporated As33S67 thin films by soft stamp hot embossing method - Kurka, Michal; Pálka, Karel; Jančálek, Jiří; Šlang, Stanislav; Vlček, Miroslav (Elsevier Science BV, 2021)
Chalcogenide As33S67 vitreous thin films prepared by thermal evaporation and spin-coating method from n-propylamine and n-hexylamine based solutions were structured using hot embossing technique with soft polydimethylsiloxane (PDMS) stamps. The influence of deposition method and conditions as well as thermal history of the samples was studied. Obtained results gave evidence that solution processed thin films can be structured at significantly lower temperatures in comparison with thermally evaporated thin films, even below Tg of the glass. Theory explaining observed phenomena based on the structural differences of solution processed and thermally evaporated thin films was proposed. Notable decrease in required embossing temperature of solution processed thin films will widen the range of chalcogenide glass compositions that can be structured by soft stamp hot embossing as well as the pool of usable substrates (such as substrates with lower temperature stability).
Strukturování z roztoku připravených a napařených tenkých vrstev As33S67 pomocí metody soft stamp hot embossing
Keywords: thin films; chalcogendie glass; hot embossing; tenké vrstvy; chalcogendová skla; hot embossing